INHIBITORY TEST OF DAYAK ONION (ELEUTHERINE BULBOSA MILL.) ESSENTIAL OIL TO THE GROWTH OF MALASSEZIA FURFUR - Syahidatun Hayati; Amanah Amanah; Rose Indriyati (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Certain fungi are normal flora on human mucosa and skin, and they require lipids for growth. One of them is Malassezia furfur, which can develop into an opportunistic infection and will take a long time to treat. The fungus may cause pityriasis versicolor, which cause scaly and discoloration of the skin. It is estimated that 40-50% from population in the tropical country is infected. Dayak onion (Eleutherine bulbosa Mill.) essential oil have the potential to treat fungal infections. This research aims to see the inhibitory potential of dayak onion essential oil (Eleutherine bulbosa Mill.) in inhibiting the growth of Malassezia furfur. Methods: This is an experimental study with a post-test control group design. The samples grouped into 7 groups. The first five treatment (P1 to P5) was given dayak onion (Eleutherine bulbosa Mill.) essential oil with a concentration of 3.125%,6.25%, 12.5%, 25%, and 50%, P6 (positive control) was given ketoconazole, and P7 (negative control) was given 10% DMSO. The inhibitory effect is measured from the diameter of the inhibitory zone, then analyzed using Kruskal-Wallis and Mann-Whitney tests. Result: The result showed that average diameter on 50% concentration is 9.25mm, 25% concentration is 7.5mm, 12.5% concentration have diameter of 4.5mm, 6.25% concentration have diameter of 3mm, 3.125% concentration with diameter of 1.75mm, positive control group with diameter of 20mm, and negative control group with diameter 0mm. Conclusions: Essential oil of dayak onion (Eleutherine bulbosa Mill.) shows inhibition of the growth of Malassezia furfur. The smallest inhibition zone diameter was 1.75 mm with concentration of 3.125%. The largest inhibition zone at a concentration of 50% with diameter of 9.25 mm. This finding showed potential effects towards antifungi treatment. Keywords: Eleutherine bulbosa Mill, Malassezia fufur, pityriasis versicolor.